Exploring Social Capital Dimensions and Participatory Budgeting in Strengthening Community Empowerment Through Village Financial and Asset Management - Pujiati, Ani; Dewi, Ade Sandra; Pahlepi, Reza; Pradana, Kenny Candra (Universitas Muhammadiyah Pontianak, 2025)
Optimizing the management of village finances and assets in an accountable, transparent, and participatory manner was key to achieving sustainable village governance. This study aimed to analyze community empowerment in the management of village finances and assets, as well as to examine the influence of social capital, including trust, norms, and social networks on community participation, both directly and indirectly through participatory budgeting. A mixed-methods approach was employed. Data were collected through observation, interviews, questionnaires, and documentation from 130 respondents selected using stratified sampling combined with Roscoe’s theory. Data analysis was conducted qualitatively using the Miles and Huberman model and quantitatively using SEM-PLS. The results indicated that community empowerment in village financial and asset management was effectively implemented through active participation in village development planning meetings, which facilitated the expression of community priorities. Transparency in budget and project information enhanced public understanding and trust in village governance. Strong social networks supported involvement in planning, decision-making, and economic empowerment, while social norms such as deliberation and mutual cooperation fostered harmony in financial management. The involvement of local labor in village projects also positively impacted the local economy. These findings emphasized the importance of integrating trust, social networks, social norms, and participatory budgeting to ensure transparent, accountable, and efficient management of village finances and assets for sustainable development.